Building Independent Culture and Financial Resilience In Islamic Education - Muhammad Hafiz; Holilur Rahman; Ummi Kulsum (STIT Attaqwa, 2024)
Self-reliant culture refers to attitudes, values, and practices that encourage individuals or groups to become more economically, socially, and emotionally independent. Building an independent culture in Islamic education is a process that involves formal and informal education, as well as daily practices in individual and community life. The aim is to create individuals who are spiritually, intellectually, and economically strong, able to make positive contributions to themselves, society, and the Islamic ummah as a whole. And financial resilience is the ability of a person or household to manage their finances well and survive in the face of unexpected financial challenges or changes in the economic situation. Financial resilience in Islamic education is a concept that emphasizes the importance of individual and community economic stability in living life, including in the context of education. This research is included in qualitative research based on literature study. The data sources in this research analyze works, books and journals related to independent culture and financial resilience in Islamic education. The results of this research are that there are five concepts involved in building a culture of independence in Islamic education, namely Spiritual Independence, Educational Independence, Economic Independence, Social Independence and Personal Independence and also important aspects in financial resilience, namely the Principles of Balance and Moderation (Wasatiyyah), Zakat, Infaq, and Sadaqah, The Importance of Knowledge, Work Ethics and Professionalism, Financial Planning and Management, Avoiding Usury.